Evaluation of reproduction for mussel Mytilus trossulus (Bivalvia: Mytilidae) in the Veselaya Bay (Tauiskaya Guba Bay, Okhotsk Sea) - V. S. Zharnikov (Известия ТИНРО, 2018)
Abundance, size composition, and terms of plankton stage were investigated for the larvae of pacific mussel in the Veselaya Bay (Okhotsk Sea) in two years with different oceanographic regime. The first larvae (density 8-30 ind./m³, shell length 75–150 μm) appeared in late June in the year with relatively high water temperature (2016) and in early July in the year with lowered temperature (2011), then their number had increased to 1750 ind./m³ in early August of 2016 and to 1320 ind./m³ in late August of 2011. Density and size composition of the spat and young mussels were examined in hanging collectors and nurseries. The growth rate change in dependence on shell length was noted. There is concluded that the hanging collectors are more effective for spat collection, while the nurseries are better for growing of littoral mussels.